Posaconazole MIC Distributions for Aspergillus fumigatus Species Complex by Four Methods: Impact of cyp51A Mutations on Estimation of Epidemiological Cutoff Values - Espinel-Ingroff, A (2018)
Fil: Espinel-Ingroff, A. VCU Medical Center, Richmond, Virginia; Estados Unidos.